MODERN INSTITUTIONS OF INTERNATIONAL LAW IN THE NEW EDITION OF THE CONSTITUTION OF THE REPUBLIC OF UZBEKISTAN: THEORETICAL AND PRACTICAL ANALYSIS (Multidisciplinary Journal of Science and Technology, 2026)
This article provides a comprehensive scholarly analysis of the integration of international legal norms into the 2023 edition of the Constitution of the Republic of Uzbekistan. The research focuses on the constitutional consolidation of the priority of universally recognized principles of international law, the direct application of international treaties, and the introduction of new legal institutions such as the "Miranda Rule" and "Habeas Corpus." The author examines the shift towards a "moderate monist" legal model and evaluates the impact of these changes on the national judicial system. The study concludes with recommendations for harmonizing domestic legislation with international human rights standards.